PENINGKATAN HASIL BELAJAR SISWA KELAS IV PADA SUBTEMA I JENIS-JENIS PEKERJAAN MELALUI MEDIA GAMBAR DI SD NEGERI 38 KOTA TERNATE - Suradin Suradin; Suhardi Abdullah; Ridwan Jusuf (PEDAGOGIK, 2023)
The purpose of this study was to determine the increase in student learning outcomes through the use of pictures media. This type of research is classroom action research. The class and subject of this study were fourth grade students at SD Negeri 38 Kota Ternate. The research data collection techniques are observation, testing and documentation. The research instrument used observation sheets in the form of teacher activity observation sheets and student activity observation sheets as well as instruments in the form of student evaluation test questions to assess student learning outcomes.The results showed that the process of learning activities through pictures media increased from cycle Ist to cycle IInd  by 18%, this can be seen from the results of the research in cycle I there were 15 students who had completed(passed the KKM) and 7 students who had not completed (not passed the KKM) with a percentage of students' classical learning completeness of 68% and in cycle II there were 19 students who had completed and 3 students who had not completed with a percentage of students' classical learning completeness of 86%. From this analysis it can be understood that the use of image media in sub-theme 1, the types of work have increased in cycle IInd. The results of this study and research could be concluded that the learning outcomes of class IV students in sub-theme I types of work through pictures media  at SD Negeri 38 Kota Ternate have increased and successed.